Análise do planejamento e controle de uma obra residencial no município de Itaituba-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This study presents the relevance of planning and control of works, in addition to highlighting the damage resulting from the lack of effectiveness in these processes. Thus, its main objective was to carry out an analysis of the planning and control of a residential construction located in a municipality in the interior of the Amazon, paying attention to aspects of schedule and cost. To this end, in addition to the characterization of the work studied, the present study included five stages: bibliographical survey; preparation of executive projects; acquisition of schedule and budget; monitoring the execution of the construction; and analysis of construction planning and control (CPC). The results revealed the effectiveness of the methods used in carrying out the work, highlighting fidelity to the schedule and budget. In terms of schedule, it was verified that the execution deadline was met, presenting a coefficient of determination (R²) of 0.9997 when comparing, graphically, the evolution of the planned and executed construction. Regarding the total cost of the construction, a reduction of 6.5% of the planned budget was observed, with the execution of the masonry being the stage that presented the greatest savings (7%).
Keywords: Obra residencial; PCO; Orçamento; Cronograma; CNPQ:: CIÊNCIAS EXATAS E DA TERRA